2014
DOI: 10.3109/1354750x.2013.867535
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of ZAR1 and SFRP4 methylation status as potentials biomarkers for diagnosis in cervical cancer: exploratory study phase I

Abstract: ZAR1 and SFRP4 qMSP could be used as potential biomarker for CC diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 29 publications
0
16
0
1
Order By: Relevance
“…To quantify the methylation level of Reprimo , quantitative methylation-specific PCR (qMSP) was performed. Amplification reactions were carried out in triplicate in a volume of 20 μL that contained 1 μL of bisulfite-modified DNA; 300 nM of each primer; 50 nM probe (Table 1 ); 0.375 U platinum Taq polymerase (Invitrogen); 100 μM of dNTPs; 100 nM ROX dye reference (Invitrogen); 8.3 mM ammonium sulfate; 33.5 mM Trizma (Sigma, St. Louis, MO); 3.35 mM magnesium chloride; 5 mM mercaptoethanol; and 0.05 % DMSO [ 30 ]. Amplifications were carried out using the following profile: 95 °C for 10 min followed by 40 cycles at 95 °C for 30 s, 59 °C for 30 s and 72 °C for 30 s. Amplification reactions were carried out in 96-well plates in the Mx3000P QPCR System (Stratagene).…”
Section: Methodsmentioning
confidence: 99%
“…To quantify the methylation level of Reprimo , quantitative methylation-specific PCR (qMSP) was performed. Amplification reactions were carried out in triplicate in a volume of 20 μL that contained 1 μL of bisulfite-modified DNA; 300 nM of each primer; 50 nM probe (Table 1 ); 0.375 U platinum Taq polymerase (Invitrogen); 100 μM of dNTPs; 100 nM ROX dye reference (Invitrogen); 8.3 mM ammonium sulfate; 33.5 mM Trizma (Sigma, St. Louis, MO); 3.35 mM magnesium chloride; 5 mM mercaptoethanol; and 0.05 % DMSO [ 30 ]. Amplifications were carried out using the following profile: 95 °C for 10 min followed by 40 cycles at 95 °C for 30 s, 59 °C for 30 s and 72 °C for 30 s. Amplification reactions were carried out in 96-well plates in the Mx3000P QPCR System (Stratagene).…”
Section: Methodsmentioning
confidence: 99%
“…In normal adult cells, it binds to Wnt morphogens and prevents their binding to corresponding transmembrane Frizzled receptor, thereby impeding the canonical Wnt pathway. However, loss of expression of sFRP4 due to promoter hypermethylation has been found in several types of cancer, such as colorectal cancer [6], bladder cancer [7], mesothelioma [8], cervical cancer [9], and ovarian cancer [10]. This promotes the upregulation of Wnt signaling, resulting in stabilization of a cytoplasmic pool of b-catenin protein, which is the signaling node of the canonical Wnt pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Hypermethylation of the SFRP4 promoter was associated with CC and may have utility for the molecular screening of cervical neoplasia (38). Brebi et al (39) revealed that SFRP4 may be used as a potential biomarker for CC diagnosis. Therefore, SFRP4 was identified to be closely associated with CC.…”
Section: Discussionmentioning
confidence: 99%